MICROPLASTIC POLLUTION OF RIVER ECOSYSTEMS IN THE FERGANA VALLEY: THE CONTRIBUTION OF UZBEK SCIENTISTS TO ASSESSING ANTHROPOGENIC IMPACTS ON THE WATER RESOURCES OF CENTRAL ASIA (Scientific journal of the Fergana State University, 2026)
Microplastic pollution represents a global environmental issue affecting aquatic ecosystems, including the rivers of Central Asia. The Fergana Valley, located in Uzbekistan, is a key region with a high level of anthropogenic pressure caused by textile industries and agriculture. Recent studies conducted by Uzbek scientists have revealed significant levels of microplastics in the region’s rivers, highlighting the need to investigate their sources, distribution, and ecological impacts. This thesis summarizes the results of studies carried out in the Fergana Valley and the tributaries of the Syr Darya River, emphasizing the contribution of Uzbek researchers to understanding this problem.